2009
DOI: 10.1007/s10570-009-9342-9
|View full text |Cite
|
Sign up to set email alerts
|

Controlled thermo-catalytic modification of regenerated cellulosic fibres using magnesium chloride Lewis acid

Abstract: The Lewis-acid catalytic reactions of magnesium chloride with regenerated cellulosic fibres under baking conditions can be interpreted using existing semi-crystalline morphological models. Reaction at 180°C is associated with chain scission, which takes place randomly within the accessible regions of the fibre structure. This causes a rapid reduction in the cellulose degree of polymerization, which stabilizes at a limiting value, analogous to that observed with wet-state mineral acid catalysed hydrolysis. A sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
(31 reference statements)
4
13
0
Order By: Relevance
“…This finding is supported by a separate kinetic analysis of the reduction in DP during hydrolysis, by previously described method, based on the Ekenstam model (Domvoglou et al 2009). The data in Table 1 also includes an estimate of LODP and the apparent fraction of reactive polymer bonds (a), which is consistent with the greater average length crystallites in lyocell compared to viscose and modal.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…This finding is supported by a separate kinetic analysis of the reduction in DP during hydrolysis, by previously described method, based on the Ekenstam model (Domvoglou et al 2009). The data in Table 1 also includes an estimate of LODP and the apparent fraction of reactive polymer bonds (a), which is consistent with the greater average length crystallites in lyocell compared to viscose and modal.…”
Section: Resultssupporting
confidence: 61%
“…The viscosity average degree of polymerization (DP) was calculated as described in previous work (Domvoglou et al 2009). Measurements were carried out on water-only treated samples and on the solid residues of hydrolysed samples following neutralization, rinsing and drying.…”
Section: Average Degree Of Polymerisationmentioning
confidence: 99%
“…Bulky, low accessibility enzyme agents are successful in achieving the desired fabric aesthetic, through attack a fibre surfaces and defects (Morgado et al 2000), but so far a replication of their mode of action has not been possible with simple organic or inorganic agents. This new study represents a continuation of previous investigations, which suggested that the local accessibility of Lewis acid salts would be reduced as a consequence of their lower diffusional mobility within the fibre structure under dry-state baking conditions, as reflected in a higher levelling-off degree of polymerisation (Domvoglou et al 2009). However, the application of salts from aqueous solution means that total initial accessibility within the fibre swollen pore structure will always be high, with sufficient polymer chains then available for catalytic attack, causing an unacceptable loss of strength.…”
Section: Introductionsupporting
confidence: 64%
“…However, the depolymerisation reaction must be carefully controlled, to reach a balance between the subsequent rate of fibrillation of the treated fibre and its tensile properties, which is difficult to achieve in practice. The application of both magnesium chloride Lewis acid and also mineral acids have been investigated (Domvoglou et al 2009;Ibbett et al 2008), which both have high accessibility within the lyocell fibre morphology. Whilst acceptable results have been achieved with both these agents under strict laboratory conditions it is considered that too many variables exist within a commercial textile processing environment for stable optimisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation